Α-Synuclein aggregation in the olfactory bulb of middle-aged common marmoset. (May 2016) - Kobayashi, Reona; Takahashi-Fujigasaki, Junko; Shiozawa, Seiji; Hara-Miyauchi, Chikako; Inoue, Takashi; Okano, Hirotaka James; Sasaki, Erika; Okano, Hideyuki
Highlights: Aggregation of α-synuclein is detectable in middle-aged marmoset olfactory bulb. Aggregated α-synuclein is mislocalized in perikarya of olfactory bulb neurons. α-Synuclein also accumulates in hippocampus of middle-aged marmoset. We did not observe α-synuclein accumulation in substantia nigra in this age group. Abstract: The synaptic protein α-synuclein has been identified as a major component of Lewy bodies, a pathological hallmark of Parkinson's disease (PD). Prior to the formation of Lewy bodies, mislocalization and aggregation of the α-synuclein in brain tissue is frequently observed in various neurodegenerative diseases. Aberrant accumulation and localization of α-synuclein are also observed in the aging human brain, for which reason aging is regarded as a risk factor for neurodegenerative disease. To investigate changes in α-synuclein properties in the aging brain, we compared α-synuclein immunoreactivity in brain tissue of young (2-years-old) and middle-aged (6-years-old) common marmoset ( Callithrix jacchus ). Our analyses revealed marked changes in α-synuclein immunoreactivity in the olfactory bulb of common marmosets of these age cohorts. Perikaryal α-synuclein aggregations were formed in the olfactory bulb in middle-aged animals. We also observed signals of α-synuclein accumulation in hippocampus in this cohort; however, unlike in the olfactory bulb, hippocampal α-synuclein signals were localized in the synaptic terminals. We did not observe either of these features in younger marmosets, which suggest that aging may play a role in these phenomena. Our results using common marmoset brain corresponded with the observation that the α-synuclein aggregations were first occurred from olfactory bulb in human normal aged and PD brain. Therefore, common marmoset is expected as useful model for α-synuclein pathology.